Metal Sprays and Spray Deposition - Henein, Hani; Uhlenwinkel, Volker; Fritsching, Udo (Springer International Publishing : Imprint: Springer, 2017)
This book describes and illustrates metal spray and spray deposition from the process engineering, metallurgical, and application viewpoints. The authors include step-by-step fundamental information for the metal spray process and detail current engineering developments and applications. They offer industry insight on non-equilibrium solidification processes for yielding stable metal structures and properties. .
Keywords: Materials science.; Chemical engineering.; Industrial engineering.; Metals.; Materials -- Surfaces.; Thin films.; elektronické knihy; electronic books